P0098CHANGES OF PERICYTE IN AGING KIDNEY. (6th June 2020) - Kim, Hyung Duk; Kim, Eun Nim; JIN, YONGJIE; Lim, Ji Hee; Kim, Yaeni; Ban, Tae Hyun; Park, Cheol Whee; Choi, Bum Soon
Abstract: Background and Aims: In aging kidney, oxidative stress and inflammation lead to a decrease in renal function. Recent studies related to the aging process of the kidneys have shown that pericyte is a progenitor cell of myofibroblast, and the relationship between renal fibrosis and pericyte has been reported. In this study, we investigated the pericytes changes in aging kidneys and mechanism of aging-related pericyte changes. Method: In vivo study, 2, 24-months-old mice and 18-month-old mice treated with pentoxifylline for 6 months were analyzed with western blot. And renal biopsy from KT donors were analyzed. Donors under age 25 were assigned to young group and donors over age 60 to old group. Results: Changes of pericytes in mice and human renal tissues were consistent with those in the aging model. In the old age group, pericytes were decreased and interstitial fibrosis was increased. Western blot analysis in mice kidney revealed that IL-1β, IL-6 and TNF-α were significantly increased in old age and significantly decreased in pentoxifylline group. Angiopoietin 2 was increased in old age group and decreased in pentoxifylline group. Conclusion: In aging kidney, pericytes have been shown to exhibit numerical reduction and loss of perivascular location as in the aging mice model. These changes in pericytes are thought to be induced by angiopoietin 2 excretion.